Chromosome numbers and meiotic studies in species of Senecio (Asteraceae) from Argentina - López, Mariana G. (2005)
Meiotic chromosome counts, chromosomal behaviour and meiotic configurations of ten taxa of Senecio from Argentina were examined. Most counts are original: S. crepidifolius DC., S. francisci Phil. and S. octolepis Griseb. var. saltensis (Hicken) Cabrera & Zardini have 2n = 40, and S. chrysolepis Phil., 2n = 80 + 8B. We confirmed previous reports for S. deferens Griseb. (2n = 40 + 4B), S. filaginoides DC. var. filaginoides (2n = 40), S. hieronymi Griseb. (2n = 40 + 7B), S. pampeanus Cabrera (2n = 40) and S. rudbeckiifolius Meyen & Walp. (2n = 40 + 7B). In S. bracteolatus Hook. & Arn. var. bracteolatus, we found a new number (2n = 40) that differs from the one cited previously. In four species, numerical polymorphisms for B-chromosomes were observed. Several of the analysed species presented secondary bivalent association. This phenomenon, together with other evidence, supports x = 5 as the basic chromosome number. The number of chiasmata and their positions were also surveyed, with the finding that open bivalents were the most frequent meiotic figures and terminal chiasmata the preferential position. These features are related to recombination rate, and the success and persistence of these polyploids. We discuss some systematic and evolutionary aspects in the light of cytogenetic data and conclude that polyploidy is the major force modelling the chromosome evolution within this genus.